Mildew-proof diatomite absorbent pad and preparation method thereof

By optimizing the raw material ratio and preparation method of diatomaceous earth water absorption pad, combined with high temperature and high pressure treatment and the use of anti-mold agents, the problems of high preparation cost, insufficient flexibility and unfast drying of diatomaceous earth water absorption pad are solved, and the water absorption pad is realized It has a comprehensive performance of quick drying, high strength, good flexibility, good formaldehyde removal and strong anti-mold effect.

CN119390415APending Publication Date: 2025-02-07GUANGXI FENGPU TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411519399.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing diatomaceous earth water-absorbing pads are cost-effective, have insufficient flexibility, and do not dry quickly. The use of silver-containing anti-mold agents can easily affect the appearance.

Method used

By optimizing the raw material ratio and preparation method, limestone is used as the binder, combined with high temperature and high pressure treatment to form small pores produced by silicon calcium crystals and carbon dioxide gas, thereby improving the strength and flexibility of the water-absorbing pad. At the same time, anti-mold agent composed of silicone quaternary ammonium salt, silver ions, cellulase, chitinase and nano zinc oxide are used to prevent the growth of mold and bacteria without affecting the appearance.

Benefits of technology

The diatomaceous earth water absorbing pad has fast drying, high strength, hard but flexible, good formaldehyde removal effect, high stability and strong sterilization effect, and anti-mold agents effectively prevent mold and bacteria from growing without affecting the color of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107621460000061
    Figure BDA0005107621460000061
  • Figure BDA0005107621460000082
    Figure BDA0005107621460000082
  • Figure BDA0005107621460000091
    Figure BDA0005107621460000091
Patent Text Reader

Abstract

The invention discloses a mildew-proof diatomite absorbent pad and a preparation method thereof, and relates to the technical field of absorbent pads and preparation methods thereof. The mildew-proof diatomite absorbent pad comprises the following raw materials: 15-20% of quartz, 50-65% of diatomite, 5-10% of paper pulp fiber, 1-3% of environment-friendly color paste and 7-19% of limestone. The preparation process comprises the following steps: adding water into the raw materials, grinding, mixing, stirring, vibrating by a vibrating screen, performing vacuum dehydration, compressing and dehydrating, cutting, performing high-temperature and high-pressure treatment, drying, sanding, cutting, washing a plate with a mildew preventive, drying, engraving, and performing color printing to obtain a finished product. By optimizing the raw materials, the proportion and the preparation method of the water-absorbing pad and optimizing the existing mildew preventive, the problems that the existing diatomite water-absorbing pad is high in preparation cost, insufficient in flexibility and not quick to dry, and the appearance is easily influenced by using a silver-containing mildew preventive are solved; the diatomite absorbent pad prepared by the method has the advantages of quick drying, high strength, hardness but flexibility, good formaldehyde removal effect, high stability and good mildew-proof and sterilizing effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water absorbent pads and preparation methods thereof, in particular to a mildew-proof diatomaceous earth water absorbent pad and a preparation method thereof. Background Art

[0002] In daily life, we often use absorbent foot pads in homes, hotels, shopping malls, cars and other places. The materials commonly used for foot pads are: chemical fiber, leather, PVC, rubber, linen, etc. Foot pads made of these materials have certain advantages, but they also have defects such as being too soft, easy to deform, having a strong smell, poor water absorption, and not drying quickly. Therefore, foot pads with diatomaceous earth as the main material came into being. Diatomaceous earth is a siliceous sedimentary rock of biological origin, mainly composed of the remains of ancient diatoms, and its main component is silicon dioxide. Because the internal structure of diatomaceous earth has many micropores and large pore size, diatomaceous earth has strong adsorption performance and permeability, which can reflect the advantages of moisture absorption, moisture absorption, odor elimination, decomposition of formaldehyde harmful substances, clean air, and regulating space humidity. It is a very popular environmentally friendly material and has been used in absorbent foot pads.

[0003] In the prior art, Patent 201611218896.6 discloses a diatomaceous earth absorbent pad and a preparation method thereof. The patent mainly uses diatomaceous earth, glass fiber, and organic glue as the main raw materials for preparation, and is baked at 50-55°C during preparation; Patent 201710624731.7 discloses a diatomaceous earth moisture-absorbing foot pad and a preparation method thereof. The patent mainly uses diatomaceous earth, obsidian, expanded perlite, bagasse, and adhesive as raw materials. During preparation, the raw materials are mixed and frozen at -5°C to 0°C; Patent 201711368103.3 discloses a diatomaceous earth foot pad and a preparation method thereof. The patent mainly uses diatomaceous earth, modified zeolite, tourmaline, bamboo charcoal, flax, and adhesive. During preparation, the raw materials are mixed and frozen at -3°C to -1°C.

[0004] The above patents can prepare water-absorbent foot pads with good mechanical properties, but there are also the following problems: first, additional binders need to be added to the raw materials, and most of them use diatomaceous earth with a high silicon content, which is expensive, resulting in increased raw material costs and is not conducive to large-scale production; second, although the above-mentioned foot pads are strong and hard, they lack flexibility and cannot fit well to the surface when used in some non-flat places, which limits the places of use; third, they are highly absorbent but not quick-drying.

[0005] In addition to the above problems, the existing diatomaceous earth absorbent foot pads are prone to breeding bacteria and mold when used in some shared places, causing odor and even shortening the service life, which seriously affects the user experience. In the prior art, silver ion-containing mildew inhibitors are often used for mildew and antibacterial, but silver ions are prone to oxidation and discoloration when exposed to light, which will affect the color of the absorbent pads and reduce their aesthetics after long-term use.

[0006] Therefore, the present invention provides a mildew-proof diatomaceous earth water-absorbing pad and a preparation method thereof to solve the above problems. Summary of the invention

[0007] In view of the above shortcomings, the present invention provides a mildew-proof diatomite absorbent pad and a preparation method thereof, which solves the problems of high preparation cost, insufficient flexibility, slow drying and the use of silver-containing mildew inhibitors that the existing diatomite absorbent pads are easy to affect the appearance. The specific technical scheme is as follows:

[0008] A method for preparing a mildew-proof diatomaceous earth water-absorbing pad comprises the following process flow:

[0009] Raw material grinding - mixing - double stirring - vibration screen vibration - vacuum dehydration - compression dehydration - high temperature and high pressure - drying - sanding - cutting - mildew-proof agent washing - drying - engraving - color printing - finished product;

[0010] The mildew preventer comprises the following raw materials in parts by weight: 10-20 parts of organosilicon quaternary ammonium salt, 1-5 parts of silver ions, 10-15 parts of cellulase, 5-10 parts of chitinase and 1-3 parts of nano zinc oxide.

[0011] Preferably, the temperature of the high temperature and high pressure treatment is 165-180°C, the pressure is 1-2MPa, and the treatment time is 20-24h.

[0012] Preferably, the drying is to dry the internally crystallized slab to a moisture content of ≤12%.

[0013] Preferably, the mildew-proofing agent for washing the slab is to mix the mildew-proofing agent and water in a volume ratio of 1:80-100 and then wash the slab.

[0014] Preferably, the organosilicon quaternary ammonium salt is tributyl organosilicon quaternary ammonium salt or dimethyl hexadecyl organosilicon quaternary ammonium salt.

[0015] Preferably, the silver ion is silver nitrate or silver chloride.

[0016] The invention also provides a mildew-proof diatomaceous earth water-absorbing pad, which comprises the following raw materials by weight percentage: 15-20% of quartz, 50-65% of diatomaceous earth, 5-10% of pulp fiber, 1-3% of environmentally friendly color paste and 7-19% of limestone.

[0017] Preferably, the length of the pulp fibers is ≥5 mm.

[0018] Preferably, the diatomaceous earth consists of white diatomaceous earth and yellow diatomaceous earth, and the weight ratio of the white diatomaceous earth to the yellow diatomaceous earth is 1:2-5.

[0019] Preferably, the white diatomaceous earth has a silicon content of 65-75%, a bulk density of 0-25, and a mesh size of 300-350 meshes; the yellow diatomaceous earth has a silicon content of 25-45%, a bulk density of 0-20, and a mesh size of 200-250 meshes.

[0020] The preparation method of the mildew preventer comprises the following steps: adding organic silicon quaternary ammonium salt to water of 5-10 times by weight, stirring at a speed of 800-1000 rpm for 5-10 minutes, to obtain solution A; adding silver ions, cellulase, chitinase and nano zinc oxide to water of 10-20 times by weight, mixing and stirring at a speed of 2000-2500 rpm for 20-30 minutes, to obtain solution B; and mixing solution A and solution B, stirring at a speed of 800-1000 rpm for 10-20 minutes, to obtain the mildew preventer.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention optimizes the raw materials, proportions and preparation method of the absorbent pad and optimizes the existing mildew inhibitor, thereby solving the problems of high preparation cost, insufficient flexibility, slow drying and easy effect of using silver-containing mildew inhibitor on the existing diatomaceous earth absorbent pad. The diatomaceous earth absorbent pad prepared by the method of the present invention has the advantages of quick drying, high strength, hardness but not lacking flexibility, good formaldehyde removal effect, high stability and good mildew and sterilization effect.

[0023] 2. The raw material of the present invention contains limestone, which will become slaked lime under high temperature and high pressure conditions and has adhesiveness. Therefore, a water-absorbing pad can be made without adding an adhesive, thereby achieving the purpose of reducing costs. At the same time, the diatomaceous earth used in the present invention is composed of white diatomaceous earth and yellow diatomaceous earth, that is, yellow diatomaceous earth with a lower price is used instead of white diatomaceous earth for production, which can further reduce production costs.

[0024] 3. The present invention subjects the slab to high temperature and high pressure treatment, and the quartz, diatomaceous earth and limestone in the raw materials undergo a chemical reaction under the action of high temperature and high pressure to form silicon-calcium crystals. At the same time, the pulp fibers and the silicon-calcium crystals are mutually attracted and connected, and are interwoven together to form a mesh porous structure with high strength and high stability, so that the obtained absorbent pad has high strength and high stability. At the same time, the limestone also produces carbon dioxide gas under high temperature, and the small holes produced by the carbon dioxide gas increase the flexibility of the absorbent pad. Therefore, the silicon-calcium crystals produced under high temperature and high pressure and the small holes produced by the carbon dioxide gas together make the obtained absorbent pad hard but not lacking in flexibility, and can be used in more places.

[0025] 4. The interior of the absorbent pad of the present invention is a porous structure, which can quickly adsorb and remove formaldehyde and bacteria, and the holes produced by carbon dioxide also accelerate drying, so that the absorbent pad can be restored to a dry state in a short time, which is suitable for humid weather in the south.

[0026] 5. The mildew inhibitor of the present invention can effectively prevent and treat various molds such as Aspergillus niger, Aspergillus terreus, Penicillium variotii, Penicillium funiculum, Aureobasidium short-stalked and Chaetomium globosum, as well as bacteria such as Escherichia coli and Staphylococcus aureus, with good control effect, and the use of the mildew inhibitor will not cause the product to change color and affect its appearance. Among them, organosilicon quaternary ammonium salt, silver ions, cellulase, chitinase and nano zinc oxide cooperate with each other, synergistically enhance the effect, can inhibit and kill various molds, and have a long-lasting effect. At the same time, nano zinc oxide has ultraviolet absorption and antioxidant effects, can prevent silver ions from changing color when encountering light and oxidation, and then prevent the water-absorbing pad from changing color. In addition, organosilicon quaternary ammonium salt can not only inhibit and kill molds, but also make nano zinc oxide disperse quickly, so that nano zinc oxide can play a role efficiently. DETAILED DESCRIPTION

[0027] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0028] The following raw materials are all commercially available.

[0029] Example 1

[0030] The raw materials of a mildew-proof diatomaceous earth water-absorbing pad in this embodiment include, by weight percentage, 15% quartz, 65% diatomaceous earth, 10% pulp fiber, 3% environmentally friendly color paste, and 7% limestone.

[0031] The diatomite is composed of white diatomite and yellow diatomite, the weight ratio of white diatomite to yellow diatomite is 1:2, the silicon content of white diatomite is 65%, the bulk density is 0, the mesh size is 300, the silicon content of yellow diatomite is 25%, the bulk density is 20, the mesh size is 200; the length of pulp fiber is 5mm. Environmentally friendly color paste has a coloring effect, and can be produced to meet the color requirements of different customers for absorbent pads.

[0032] The preparation method comprises the following steps:

[0033] S1. Weigh the above raw materials according to weight percentage, add water to each raw material, grind for 2 hours, mix, and stir at a speed of 1440 rpm for 10 minutes, then vibrate on a vibrating screen to obtain a mixed slurry;

[0034] S2, vacuum dehydrating and compressing the mixed slurry to form a preliminary plate shape, cutting off irregular edges and corners to obtain a square slab;

[0035] S3, subjecting the slab to high temperature and high pressure treatment, wherein the temperature of the high temperature and high pressure treatment is 165° C., the pressure is 1 MPa, and the treatment time is 24 hours to obtain an internally crystallized slab;

[0036] S4, drying the internally crystallized slab to a moisture content of 12%, sanding, cutting, mixing a mildew-proof agent and water in a volume ratio of 1:80 and then washing the slab, continuing to dry to a moisture content of 12%, engraving, color printing, and obtaining a finished product.

[0037] The mildew preventer comprises the following raw materials in parts by weight: 10 parts of tributyl silicone quaternary ammonium salt, 1 part of silver nitrate, 10 parts of cellulase, 5 parts of chitinase and 1 part of nano zinc oxide.

[0038] The preparation method of the mildew preventer comprises the following steps: adding tributyl organosilicon quaternary ammonium salt to water of 5 times by weight, stirring at a speed of 800 rmp for 5 minutes, and obtaining solution A; adding silver nitrate, cellulase, chitinase and nano zinc oxide to water of 10 times by weight, mixing and stirring at a speed of 2000 rmp for 20 minutes, and obtaining solution B; and mixing solution A and solution B, and stirring at a speed of 800 rmp for 10 minutes, and obtaining the mildew preventer.

[0039] Example 2

[0040] The raw materials of a mildew-proof diatomaceous earth water-absorbing pad in this embodiment include, by weight percentage, 20% quartz, 50% diatomaceous earth, 8% pulp fiber, 3% environmentally friendly color paste, and 19% limestone.

[0041] The diatomite is composed of white diatomite and yellow diatomite, the weight ratio of white diatomite to yellow diatomite is 1:5, the silicon content of white diatomite is 75%, the bulk density is 25, the mesh number is 350, the silicon content of yellow diatomite is 45%, the bulk density is 20, the mesh number is 250; the length of pulp fiber is 7mm. Environmentally friendly color paste has a coloring effect, and can be produced to meet the color requirements of different customers for absorbent pads.

[0042] The preparation method comprises the following steps:

[0043] S1. Weigh the above raw materials according to weight percentage, add water to each raw material, grind for 2 hours, mix, and stir at a speed of 1500 rpm for 8 minutes, then vibrate with a vibrating screen to obtain a mixed slurry;

[0044] S2, the mixed slurry is subjected to vacuum dehydration and compression dehydration to initially form a plate, and irregular edges and corners are cut off to obtain a square slab;

[0045] S3, subjecting the slab to high temperature and high pressure treatment, wherein the temperature of the high temperature and high pressure treatment is 180° C., the pressure is 2 MPa, and the treatment time is 20 h, to obtain an internally crystallized slab;

[0046] S4, drying the internally crystallized slab to a moisture content of 10%, sanding, cutting, mixing a mildew-proof agent and water in a volume ratio of 1:100 and then washing the slab, continuing to dry to a moisture content of 10%, engraving, color printing, and obtaining a finished product.

[0047] The mildew preventer comprises the following raw materials in parts by weight: 20 parts of dimethyl hexadecyl organosilicon quaternary ammonium salt, 5 parts of silver chloride, 15 parts of cellulase, 10 parts of chitinase and 3 parts of nano zinc oxide.

[0048] The preparation method of the mildew preventer comprises the following steps: adding dimethyl hexadecyl organosilicon quaternary ammonium salt to water with a total weight of 10 times, stirring at a speed of 1000 rmp for 10 minutes, and obtaining solution A; adding silver chloride, cellulase, chitinase and nano zinc oxide to water with a total weight of 20 times, mixing and stirring at a speed of 2500 rmp for 30 minutes, and obtaining solution B; and mixing solution A and solution B, and stirring at a speed of 1000 rmp for 20 minutes, and obtaining the mildew preventer.

[0049] Example 3

[0050] The raw materials of a mildew-proof diatomaceous earth water-absorbing pad in this embodiment include, by weight percentage, 16% quartz, 60% diatomaceous earth, 8% pulp fiber, 1% environmentally friendly color paste and 15% limestone.

[0051] The diatomite is composed of white diatomite and yellow diatomite, the weight ratio of white diatomite to yellow diatomite is 1:3, the silicon content of white diatomite is 60%, the bulk density is 25, the mesh number is 300, the silicon content of yellow diatomite is 45%, the bulk density is 0, the mesh number is 250; the length of pulp fiber is 7mm. Environmentally friendly color paste has a coloring effect, and can be produced to meet the color requirements of different customers for absorbent pads.

[0052] The preparation method comprises the following steps:

[0053] S1. Weigh the above raw materials according to weight percentage, add water to each raw material, grind for 2 hours, mix, and stir at a speed of 1400 rpm for 12 minutes, then vibrate with a vibrating screen to obtain a mixed slurry;

[0054] S2, the mixed slurry is subjected to vacuum dehydration and compression dehydration to initially form a plate, and irregular edges and corners are cut off to obtain a square slab;

[0055] S3, subjecting the slab to high temperature and high pressure treatment, wherein the temperature of the high temperature and high pressure treatment is 175° C., the pressure is 1 MPa, and the treatment time is 24 hours, to obtain an internally crystallized slab;

[0056] S4, drying the internally crystallized slab to a moisture content of 10%, sanding, cutting, mixing a mildew-proof agent and water in a volume ratio of 1:90 and then washing the slab, continuing to dry to a moisture content of 12%, engraving, color printing, and obtaining a finished product.

[0057] The mildew preventer comprises the following raw materials in parts by weight: 15 parts of tributyl silicone quaternary ammonium salt, 4 parts of silver chloride, 12 parts of cellulase, 6 parts of chitinase and 2 parts of nano zinc oxide.

[0058] The preparation method of the mildew preventer comprises the following steps: adding tributyl organosilicon quaternary ammonium salt to water of 8 times by weight, stirring at a speed of 900 rmp for 6 minutes, and obtaining solution A; adding silver chloride, cellulase, chitinase and nano zinc oxide to water of 15 times by weight, mixing and stirring at a speed of 2200 rmp for 23 minutes, and obtaining solution B; and mixing solution A and solution B, and stirring at a speed of 900 rmp for 15 minutes, and obtaining the mildew preventer.

[0059] The thickness of the water-absorbing pad obtained in the above embodiment is about 9 mm.

[0060] 1. Mechanical properties of the water-absorbent pad of the present invention

[0061] The absorbent pads prepared in Example 1, Example 2 and Example 3 were tested for density, porosity, strength, flexibility and other properties, and their appearance was observed. The results are shown in Table 1:

[0062] Among them, the strength test is carried out in accordance with GB / T 50107-2010, and the density test is carried out in accordance with GB / T 11970-1997; the flexibility is to apply an external force to the absorbent pad to cause deformation, then remove the external force and observe whether the absorbent pad returns to its original shape after the external force is removed.

[0063] Table 1 Mechanical properties of water-absorbing pads in the examples

[0064]

[0065] Remarks: Technical requirements: density 0.8-1.2g / cm3, porosity ≥50%, transverse strength ≥10MPa, longitudinal strength ≥8MPa.

[0066] Table 1 shows that the density, porosity and strength of the diatomite absorbent pad prepared by the present invention all meet the technical requirements, and the appearance has no cracks, peeling and stratification, and has good flexibility.

[0067] 2. Determination of antibacterial activity of the absorbent pad of the present invention

[0068] The absorbent pads prepared in Example 1, Example 2 and Example 3 were subjected to an antibacterial effect test with an oscillation contact time of 1 hour. The detection method was carried out in accordance with the standard ASTM E2149-2020, and the detected bacteria were Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 6538. The bacterial reduction rate was calculated, and the results are shown in Table 2:

[0069] Table 2 Antibacterial activity test results

[0070] project E. coli reduction rate (%) Staphylococcus aureus reduction rate (%) Example 1 33 57 Example 2 32 54 Example 3 37 58

[0071] 3. Test of formaldehyde purification performance of the absorbent pad of the present invention

[0072] The formaldehyde purification performance of the absorbent pads prepared in Example 1, Example 2 and Example 3 was tested according to JC / T1074-2008 "Purification Performance of Indoor Air Purification Function Coating Materials". The experimental sample size was 1m 2 (Sample double-sided test), sealed chamber volume 1m 3 , Experimental conditions: temperature (20±2℃). The results are shown in Table 3:

[0073] Table 3 Formaldehyde purification performance test results

[0074] project Standard requirements (Class I) Formaldehyde purification performance (%) in conclusion Example 1 ≥75 90.4 conform to Example 2 ≥75 90.3 conform to Example 3 ≥75 90.3 conform to

[0075] 4. Water absorption performance test of the water absorbent pad of the present invention

[0076] The water absorption rate, water absorption speed and drying speed of the water absorbent pads prepared in Example 1, Example 2 and Example 3 were tested. The results are shown in Table 4.

[0077] Water absorption test method: Place the absorbent pad in a drying oven at 105±5℃ for 24 hours, take it out and place it in a desiccator to cool to room temperature, weigh the mass of the absorbent pad m1, and round it to 0.1g; soak it in room temperature water (20±5℃) for 24 hours; take the absorbent pad out of the water, carefully wipe off the water attached to the surface of the absorbent pad with a wet towel, and immediately weigh the mass of the saturated absorbent pad m3, and round it to 0.1g; the water absorption rate is calculated according to the formula

[0078] Water absorption speed: Pour 125 ml of room temperature water (20±5℃) on the absorbent pad and use a stopwatch to record the time it takes for the water marks on the surface of the absorbent pad to disappear.

[0079] Drying speed: Allow the absorbent pad to absorb 125 ml of room temperature water (20±5°C) and dry naturally at room temperature to the original weight. Record the drying time.

[0080] Table 4 Water absorption performance of the absorbent pad of the embodiment

[0081] project Water absorption (%) Water absorption speed (min) Drying speed(min) Example 1 55 41 62 Example 2 51 42 64 Example 3 56 40 61

[0082] Remarks: Technical requirements: Water absorption ≥ 45%.

[0083] Table 2, Table 3 and Table 4 show that the water-absorbing pad of the present invention has the advantages of quick drying, good sterilization effect and good formaldehyde removal effect.

[0084] Comparative Example 1: An equal amount of slaked lime was used instead of limestone, and other raw materials and preparation methods were the same as those in Example 1.

[0085] The strength, flexibility, drying speed and porosity of the absorbent pads obtained in Comparative Example 1 and Example 1 were tested respectively, and the testing methods were the same as above. The results are shown in Table 5:

[0086] Table 5 Comparison of test results of Example 1 and Comparative Example 1

[0087]

[0088] From the comparative data in the above table, it can be seen that when the same amount of slaked lime is used instead of limestone, although the overall strength is slightly higher than that of Example 1, the flexibility is insufficient and the drying time is also longer, which may be related to the inability of slaked lime to produce carbon dioxide.

[0089] Comparative Example 2: During preparation, the slab processing temperature in step S3 is 300°C, and other raw materials and preparation methods are the same as those in Example 1.

[0090] Comparative Example 3: During preparation, the slab processing temperature in step S3 is 100°C, and other raw materials and preparation methods are the same as those in Example 1.

[0091] The strength, flexibility, drying speed and porosity of the absorbent pads obtained in Comparative Example 2, Comparative Example 3 and Example 1 were tested respectively, and the testing method was the same as above. The results are shown in Table 6:

[0092] Table 6 Comparison of test results of Example 1 and Comparative Examples 2 and 3

[0093]

[0094] Table 6 shows that the processing temperature of the slab in step S3 will also affect the finished product. Only when the temperature of the present invention (165-180°C) is used can a water-absorbing pad with good properties be obtained. At 300°C, the reaction is more intense, the gas generation rate is fast, and the uneven pore generation leads to poor product flexibility. At 100°C, the reaction is slower, the gas generation rate is slow, and the uneven pore generation also leads to poor product flexibility. In addition, too high or too low a temperature will also affect the appearance, resulting in cracks or delamination.

[0095] Comparative Example 4: The raw materials of this comparative example include, by weight percentage, quartz 16%, diatomaceous earth 66%, pulp fiber 10%, environmentally friendly color paste 3% and limestone 5%, that is, compared with Example 1, the proportion of limestone is reduced and the total proportion of quartz and diatomaceous earth is increased. The preparation method is the same as that of Example 1.

[0096] Comparative Example 5: The raw materials of this comparative example include, by weight percentage, quartz 15%, diatomaceous earth 50%, pulp fiber 10%, environmentally friendly color paste 3% and limestone 22%, that is, compared with Example 1, the proportion of limestone is increased and the total proportion of quartz and diatomaceous earth is reduced. The preparation method is the same as that of Example 1.

[0097] Comparative Example 6: The raw materials of this comparative example include, by weight percentage, quartz 15%, diatomaceous earth 50%, pulp fiber 8%, environmentally friendly color paste 3% and limestone 24%, that is, compared with Example 1, the proportion of limestone is increased and the total proportion of quartz and diatomaceous earth is reduced. The preparation method is the same as that of Example 1.

[0098] Comparative Example 7: The raw materials of this comparative example include, by weight percentage, quartz 15%, diatomaceous earth 50%, pulp fiber 8%, environmentally friendly color paste 1% and limestone 26%, that is, compared with Example 1, the proportion of limestone is increased and the total proportion of quartz and diatomaceous earth is reduced. The preparation method is the same as that of Example 1.

[0099] The strength and flexibility of the absorbent pads obtained in Comparative Examples 4 to 7 and Example 1 were tested respectively, and the testing method was the same as above. The results are shown in Table 7:

[0100] Table 7 Comparison of test results of Example 1 and Comparative Examples 4 to 7

[0101]

[0102] Remarks: Technical requirements: transverse strength ≥10MPa, longitudinal strength ≥8MPa.

[0103] Table 7 shows that the proportion of limestone, quartz and diatomaceous earth will also have an impact on the finished product. The data of Comparative Example 4 shows that when the proportion of limestone decreases and the total proportion of quartz and diatomaceous earth increases, cracks will appear in the product, and the strength cannot meet the technical requirements, and the flexibility is poor; the data of Comparative Examples 5, 6, and 7 show that when the proportion of limestone increases and the total proportion of quartz and diatomaceous earth decreases, although the product strength can meet the technical requirements, the product appearance and flexibility are not good. The applicant unexpectedly discovered that only when the amount of limestone added is 7-19% and the total proportion of quartz and diatomaceous earth is 70-80%, the strength, flexibility and appearance of the absorbent pad can meet the technical requirements at the same time.

[0104] The data in Tables 6 and 7 show that the raw materials, proportions and processing temperature of the slabs of the present invention are closely related. Changing any one of them will result in the performance of the water-absorbing pad not meeting the requirements. The applicant has found a suitable match among the three after repeated experiments and explorations.

[0105] V. Test of the Anti-mildew Performance of the Water-Absorbent Pad of the Present Invention

[0106] According to GB / T 35469-2017 "Test Method for Mildew Resistance of Building Wood-Plastic Composite Materials", the mildew resistance of the absorbent pads prepared in Examples 1 to 3 was tested, and a comparative example was set for comparison. The comparative example is set as follows:

[0107] Comparative Example 8: The mildew preventer used in the absorbent pad of Example 1 does not contain organosilicon quaternary ammonium salt, and other raw materials of the mildew preventer are the same as those in Example 1;

[0108] Comparative Example 9: The mildew preventer used in the absorbent pad of Example 1 does not contain nano zinc oxide, and the other raw materials of the mildew preventer are the same as those of Example 1;

[0109] Comparative Example 10: The mildew preventer used in the absorbent pad of Example 1 does not contain organosilicon quaternary ammonium salt and nano zinc oxide, and the other raw materials of the mildew preventer are the same as those in Example 1;

[0110] A blank group, i.e., no mildewcide was applied to the absorbent pad of Example 1;

[0111] The mildew-proof effect of the above-mentioned absorbent pads was tested. After the test, the absorbent pads of the above-mentioned embodiments and comparative examples were subjected to an aging test according to the provisions of GB / T 29365-2012. After aging, the surface was washed with sterile water and dried. Then, the mildew-proof test was continued using the method of GB / T35469-2017, and the color change of the aged absorbent pad was observed. The results are shown in Table 8:

[0112] Table 8 Anti-mildew effect of each group

[0113] Example Mildew resistance level before aging Mildew resistance level after aging Discoloration after aging Example 1 0 1 No discoloration Example 2 1 2 No discoloration Example 3 0 1 No discoloration Comparative Example 8 2 4 Slight discoloration Comparative Example 9 2 4 Severe discoloration Comparative Example 10 3 4 Severe discoloration Blank Group 4 4 -

[0114] Note: Level 0, no growth; Level 1, moldy area <10% (trace growth); Level 2, moldy area 10-30% (small growth); Level 3, moldy area 30-60% (moderate growth); Level 4, moldy area ≥60% (heavy growth).

[0115] Table 8 shows that the various raw materials in the mildew inhibitor of the present invention cooperate with each other, which can not only prevent mildew for a long time but also maintain the beauty of the product.

[0116] In summary, the present invention solves the problems of high preparation cost, insufficient flexibility and slow drying of the existing diatomite water-absorbing pad by optimizing the raw materials, proportions and preparation methods. The diatomite water-absorbing pad prepared by the method of the present invention has the advantages of quick drying, high strength, hardness but not lacking flexibility, good formaldehyde removal effect, high stability and strong bactericidal effect. In addition, the raw materials of the present invention contain limestone, which will become slaked lime under high temperature and high pressure conditions and has adhesiveness. Therefore, the water-absorbing pad can be made without adding a binder, thereby achieving the purpose of reducing costs. At the same time, the diatomite used in the present invention is composed of white diatomite and yellow diatomite, that is, yellow diatomite with a cheaper price is used to replace white diatomite for production, which can further reduce production costs.

[0117] The present invention treats the slab with high temperature and high pressure, and the quartz, diatomaceous earth and limestone in the raw materials react chemically under the action of high temperature and high pressure to form silicon calcium crystals. At the same time, the pulp fibers and silicon calcium crystals are mutually pulled and connected, and interwoven together to form a mesh porous structure with high strength and high stability, so that the prepared water-absorbing pad has high strength and high stability. At the same time, the limestone produces carbon dioxide gas under high temperature, which further increases the number of small holes in the mesh porous structure, thereby increasing the flexibility of the water-absorbing pad. Therefore, the silicon calcium crystals produced under high temperature and high pressure and the small holes produced by the carbon dioxide gas together make the prepared water-absorbing pad hard but not lacking in flexibility, and can be applied to more places. The interior of the water-absorbing pad of the present invention is a porous structure, which can quickly adsorb and remove formaldehyde and bacteria, and the holes produced by the carbon dioxide also accelerate drying, so that the water-absorbing pad can be restored to a dry state in a short time, which is suitable for humid weather in the south.

[0118] The mildew inhibitor of the present invention can effectively prevent and treat various molds such as Aspergillus niger, Aspergillus terreus, Penicillium variotii, Penicillium funiculum, Aureobasidium short-stalked and Chaetomium globosum, as well as bacteria such as Escherichia coli and Staphylococcus aureus, and has good control effect. The use of the mildew inhibitor will not cause the product to change color and affect its appearance. Among them, the organosilicon quaternary ammonium salt, silver ions, cellulase, chitinase and nano zinc oxide cooperate with each other, synergistically enhance the effect, can inhibit and kill various molds, and have a long-lasting effect. At the same time, nano zinc oxide has ultraviolet absorption and anti-oxidation effects, can prevent silver ions from changing color when encountering light and oxidation, and then prevent the water-absorbing pad from changing color. In addition, the organosilicon quaternary ammonium salt can not only inhibit and kill molds, but also make the nano zinc oxide quickly disperse, so that the nano zinc oxide can play a role efficiently, and improve the antibacterial effect.

[0119] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing a mildew-proof diatomaceous earth water-absorbing pad, characterized in that: Including the following process: Raw material grinding - mixing - double stirring - vibration screen vibration - vacuum dehydration - compression dehydration - high temperature and high pressure - drying - sanding - cutting - mildew-proof agent washing - drying - engraving - color printing - finished product; The mildew preventer comprises the following raw materials in parts by weight: 10-20 parts of organosilicon quaternary ammonium salt, 1-5 parts of silver ions, 10-15 parts of cellulase, 5-10 parts of chitinase and 1-3 parts of nano zinc oxide.

2. The method for preparing a mildew-proof diatomaceous earth water-absorbing pad according to claim 1, characterized in that: The temperature of the high temperature and high pressure treatment is 165-180° C., the pressure is 1-2 MPa, and the treatment time is 20-24 hours.

3. The method for preparing a mildew-proof diatomaceous earth absorbent pad according to claim 1, characterized in that: The drying is to dry the internally crystallized slab to a moisture content of ≤12%.

4. The method for preparing a mildew-proof diatomaceous earth water-absorbing pad according to claim 1, characterized in that: The method of washing the board with the mildew-proof agent comprises mixing the mildew-proof agent and water in a volume ratio of 1:80-100 and then washing the board blank.

5. The method for preparing a mildew-proof diatomaceous earth absorbent pad according to claim 1, characterized in that: The organosilicon quaternary ammonium salt is tributyl organosilicon quaternary ammonium salt or dimethyl hexadecyl organosilicon quaternary ammonium salt.

6. The method for preparing a mildew-proof diatomaceous earth water-absorbing pad according to claim 1, characterized in that: The silver ion is silver nitrate or silver chloride.

7. A mildew-proof diatomaceous earth absorbent pad prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The raw materials include the following by weight percentage: Quartz 15-20%, diatomaceous earth 50-65%, pulp fiber 5-10%, environmentally friendly color paste 1-3% and limestone 7-19%.

8. The mildew-proof diatomaceous earth water-absorbing pad according to claim 7, characterized in that: The length of the pulp fibers is ≥5 mm.

9. The mildew-proof diatomaceous earth absorbent pad according to claim 7, characterized in that: The diatomaceous earth consists of white diatomaceous earth and yellow diatomaceous earth, and the weight ratio of the white diatomaceous earth to the yellow diatomaceous earth is 1:2-5.

10. The mildew-proof diatomaceous earth water-absorbing pad according to claim 7, characterized in that: The white diatomite has a silicon content of 65-75%, a bulk density of 0-25, and a mesh size of 300-350; the yellow diatomite has a silicon content of 25-45%, a bulk density of 0-20, and a mesh size of 200-250.

Citation Information

Patent Citations

  • A diatomaceous earth absorbent pad and its preparation method

    CN106588105B

  • Moisture absorption floor mat with diatomaceous earth and method for preparing moisture absorption floor mat

    CN107365112A

  • A diatomaceous earth foot pad and its preparation method

    CN107986694B